Kewenangan Penyidikan Pada Tindak Pidana Korupsi Dalam Sistem Peradilan Pidana - Muhammad Romadhan; Muhammad Nugraha; Dwiky Septian; Zain Agiel Abdullah; Andreas Jona Situmorang; Derry Angling Kesuma (Consensus : Jurnal Ilmu Hukum, 2023)
For the law is made in the multitude, small and great, that it may be in harmony with the law, in order, and in certainty; and there shall be a measure, that every man may behave well. If someone does anything that is contrary to the law or deviates from the harmony, order, and peace of life, the person who does so will be punished or punished. Everyone who commits a crime will suffer physical and mental suffering as a result of this sanction of the law, which will make them a jera or a capricorn to do it again. The criminal prosecution system is not working well because it is not structurally integrated in terms of the concept of the functioning and supervision of the justice system. This makes it weak in law enforcement because it is under executive authority (government), so in some cases affected by executive power.